Synergistic Activity of Cymbopogon citratus and Mentha piperita Essential Oils against the Pinewood Nematode - Diogo Gonçalves; Tomás Cavaco; Ana Pombo; Cristina Moiteiro; Dora Martins Teixeira; Maria L. Inácio; Jorge M. S. Faria (Environmental Sciences Proceedings, 2022)
The pinewood nematode (PWN) Bursaphelenchus xylophilus is a major threat to pine forests. Research on sustainable pest management strategies is now a priority. Essential oils (EOs) are biodegradable, complex mixtures of volatiles that can show low toxicity to mammals and powerful nematicidal activities depending on their chemical composition. In the present work, the EOs of four plants were screened against the PWN, solely and in combination to identify possible synergistic interactions. The combination of Cymbopogon citratus and Mentha piperita EOs (1:1) resulted in higher activities than those of each tested solely, suggesting the occurrence of synergistic interactions between the compounds of these EOs. Research on the combination of synergistic EOs may lead to the development of plant based biopesticides with optimized activities against the PWN.